2013
DOI: 10.1007/s00737-013-0336-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conception to parenting: a systematic review and meta-synthesis of the qualitative literature on motherhood for women with severe mental illness

Abstract: The majority of women with a severe mental illness (SMI) become pregnant and have children. The aim of this systematic review and meta-synthesis was to examine the qualitative research on the experiences of motherhood in women with SMI from preconception decision making to being a mother. The experiences of the health professionals treating women with SMI were also reviewed. Eleven databases were searched for papers published up to April 25, 2012, using keywords and mesh headings. A total of 23 studies were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
198
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(217 citation statements)
references
References 52 publications
15
198
1
3
Order By: Relevance
“…Several previous studies have investigated parenting outcomes in psychosis (e.g. Dolman et al, 2013;Plant et al, 2002), however, this research tends to regard the parenting abilities of mothers who already have psychosis whereas the mediation model in the current study suggests that parenting emotional experiences may also predict levels of sub-clinical psychotic phenomena. The current study used a non-clinical population rather than a clinical sample, but due to the link between schizotypy and psychosis our findings suggest that the model should be tested in a clinical sample.…”
Section: Discussionmentioning
confidence: 65%
“…Several previous studies have investigated parenting outcomes in psychosis (e.g. Dolman et al, 2013;Plant et al, 2002), however, this research tends to regard the parenting abilities of mothers who already have psychosis whereas the mediation model in the current study suggests that parenting emotional experiences may also predict levels of sub-clinical psychotic phenomena. The current study used a non-clinical population rather than a clinical sample, but due to the link between schizotypy and psychosis our findings suggest that the model should be tested in a clinical sample.…”
Section: Discussionmentioning
confidence: 65%
“…Stigma was a repetitive theme as women struggled to identify themselves as potentially good mothers against the more prevalent societal views of mental illness. 37 In attempting to live up to societal expectations, women internalized stigma as self-stigma, thus viewing themselves as inadequate. 37 Guilt also revolved around women's fears that they may pass on their mental illness, whether genetically or environmentally.…”
Section: Serious Mental Illnessmentioning
confidence: 99%
“…37 In attempting to live up to societal expectations, women internalized stigma as self-stigma, thus viewing themselves as inadequate. 37 Guilt also revolved around women's fears that they may pass on their mental illness, whether genetically or environmentally. Across several studies, in Dolman's meta-synthesis, a recurring theme was their sense of isolation and loneliness.…”
Section: Serious Mental Illnessmentioning
confidence: 99%
“…They emphasized the importance of family support in times of their illness. Dolman, Jones, and Howard (2013) also reported on the importance of the support network for women with schizophrenia where the women reported that support alleviated some of the demands during times of illness. Social support and in particular emotional support were found to be a predictor of quality of life for people diagnosed with psychosis in a study by Caron, Lecomte, Stip, and Renaud (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, based on the meta-analytic links between accumulation of socio-economic risk and disorganized and insecure attachment (Cyr et al, 2010), a positive association was hypothesized between the sum of socio-economic risk factors and disorganized and insecure attachment. Thirdly, based on studies suggesting a protective effect of social support (Caron et al, 2005;Dolman et al, 2013) as well as based on qualitative reports of the importance of support figures in the lives of mothers with psychosis and/or HIV (Spies et al 2016), the hypothesis was tested that access to emotional support would compensate and buffer the risk of insecure and disorganized attachment. Fourthly, the hypothesis was tested that insecure and disordered attachment in this high risk population that is confronted with psychosis and/or HIV was elevated in comparison to general population samples as well as other high risk samples studied in the literature (Cyr et al, 2010;Van IJzendoorn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%